Miguel Ángel BUNES IBARRA: La batalla de Lepanto (Inebahti) vista por los otomanos, Madrid, Catarata, 2023, 189 pp., ISBN: 978-84-1352-627-0. (Revista Universitaria de Historia Militar, 2024)
Reseña de Miguel Ángel BUNES IBARRA: La batalla de Lepanto (Inebahti) vista por los otomanos, Madrid, Catarata, 2023, 189 pp., ISBN: 978-84-1352-627-0.